Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
If we know the quadratic formula, the quadratic formula is
x = [-b ± √(b²- 4ac)] / 2a
Gosh! So overwhelming! But let's look at the composition of a quadratic equation:
ax² + bx + c = 0
And we have 6x² - 3x = 1. So, what do we do? We need to put this quadratic equation into an easy form to find the value of a, b, and c to plug in to the equation.
We can just minus one on both sides to get this:
6x² - 3x - 1 = 0
Is it in the form of ax² + bx + c? Yes! a = 6, b = -3, and c = -1. Now, all we have to do is plug it into the quadratic formula.
x = [-b ± √(b²- 4ac)] / 2a
x = [-(-3) ± √((-3)²- 4(6)(-1))] / 2(6)
[3 ± √(9- 4(6)(-1))] / 12
[3 ± √(9 + 24)] / 12
[3 ± √(33)] / 12
At this point, we should just use a calculator, and recognize we have two answers because of the plus-or-minus sign! (or this sign: ±)
[3 ± √(33)] / 12
1) [3 + √(33)] / 12 = 0.73 approximately
2) [3 - √(33)] / 12 = -0.23 approximately
So, x=0.73 and x= -0.23.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.